Respostas

2014-07-11T17:08:17-03:00
Lei dos senos

 \frac{5 \sqrt{6} }{60^0}=2R \\  \\  \frac{5 \sqrt{6} }{ \frac{ \sqrt{3} }{2} }  =2R \\  \\  \frac{10 \sqrt{6} }{ \sqrt{3} } =2R \\  \\  \frac{10 \sqrt{3}. \sqrt{2}  }{ \sqrt{3} } =2R \\  \\ 10 \sqrt{2}=2R \\  \\ R= \frac{10 \sqrt{2} }{2}   \\  \\ R=5 \sqrt{2} [tex] \frac{5 \sqrt{6} }{60^0}=2R \\ \\ \frac{5 \sqrt{6} }{ \frac{ \sqrt{3} }{2} } =2R \\ \\ \frac{5 \sqrt{6} }{1} * \frac{2}{ \sqrt{3} } =2R \\ \\ \frac{10 \sqrt{6} }{ \sqrt{3} } =2R \\ \\ \frac{10 \sqrt{2}. \sqrt{3} }{ \sqrt{3} }